Inhibition of neutrophil infiltration and NETs formation ameliorates neuropsychiatric and renal dysfunction in MRL/lpr mice with lupus - Yiyao Deng; Yu Shang; Yongqiang Zhang; Delun Li; Yongle Xiong; Yan Shen; Lu Liu; Yan Ran; Pinghong He; Shuang Chen; Libo Wu; Shanshan Hu; et al. (PLoS ONE, 2026)
Background Patients with systemic lupus erythematosus often experience kidney and nervous system damage. It has been discovered that neutrophils and NETs play a significant role in lupus-related damage. However, whether inhibiting the infiltration of neutrophils into tissues can alleviate lupus-related brain and kidney damage remains unclear. Methods Lupus-prone MRL/lpr mice were assigned to four groups: MRL/MpJ control, MRL/lpr model, MRL/lpr + Avacopan, and MRL/lpr + Naringenin. Cognitive functions such as memory, emotion, and learning in the mice were assessed through open field tests, Y-maze tests, and water maze tests. Changes in kidney function were also evaluated in each group. Pathological changes in the brain and kidneys of the mice, as well as the infiltration of neutrophils and the expression of NETs-related markers NE and MPO, were observed using histopathological staining, immunohistochemistry, silver staining, and multiplex immunofluorescence staining. Additionally, changes in the expression of key inflammatory factors in the brain and kidneys were examined. Results Avacopan can improve cognitive function impairment and the progression of kidney damage in lupus-prone mice. Additionally, Avacopan has been found to reduce the infiltration of CD11b-positive and CD11b/CD16 double-positive cells into the brain and kidneys, as well as to decrease the expression of NETs-related markers NE and MPO. Notably, we observed that the main NETs marker in the kidneys of lupus mice is NE. Key inflammatory factors associated with lupus, such as IL-6, IL-17, and TNF-α, are found to be elevated in both the brain and kidney tissues of lupus mice, and Avacopan can reduce the expression of these inflammatory factors. Conclusion Neutrophils play a significant role in systemic lupus erythematosus-related brain and kidney damage. Inhibiting the infiltration of neutrophils can mitigate the inflammatory damage and NETs-related damage caused by their infiltration. However, the detailed mechanisms by which neutrophils cause tissue damage still need further clarification. For example, it remains to be explained why there is such substantial infiltration of neutrophils into tissues, what the cell signaling mechanisms involved in damage after neutrophil infiltration are, and whether there is any impact on the regulation of other immune cells such as macrophages and T lymphocytes. Further research is needed on these aspects.